REFORMULATION OF THE DUTIES AND AUTHORITIES OF THE PROSECUTOR’S COMMISSION IN INDONESIAN LEGISLATION - Suwartono, Suwartono; Efendi, Dr. Jonaedi (Acitya Wisesa: Journal of Multidisciplinary Research, 2024)
Article 2 of Presidential Regulation No. 18/2011 on the Prosecutorial Commission states that the Commission is a non-structural institution that is independent in its tasks and authorities. Although it is under and responsible to the President, this commission acts as an external supervisor of the prosecutor’s office, which is required due to frequent violations of ethical codes and abuse of authority by prosecutorial officials. The public is dissatisfied with case handling by the internal supervisor of the prosecutor’s office, so the presence of the Prosecutor’s Commission is expected. However, there is a discrepancy in the regulation of the Prosecutorial Commission. The commission, as an external supervisor, should be regulated by law to maintain a balance in constitutional law. In reality, the commission is only regulated through a Presidential Regulation, so it does not have the authority to summon and examine prosecution officials who have violated the code of ethics. This research aims to examine the duties and authorities of the Prosecutor’s Commission based on existing regulations, and to reformulate policies so that its tasks and authorities are in accordance with its expected role as an external supervisor of the prosecutor’s office. This research uses the normative juridical method, examining written law from various aspects such as theory, history, legal politics, and comparative national law. This research will also theoretically clarify the function of the prosecutor’s office in society. The Prosecutorial Commission of the Republic of Indonesia is regulated by Presidential Regulation No. 18/2011, but its autonomy has not been fully recognized because it is still responsible to the President and can only provide recommendations. Policy reformulation is required by amending Article 38 of Law No. 16/2014 so that the Prosecutorial Commission is governed by a stronger special law, allowing it to perform its duties independently.